Vertical Contracting with Endogenous Market Structure - Marco Pagnozzi; Salvatore Piccolo; Markus Reisinger (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
A manufacturer chooses the optimal retail market structure and bilaterally and secretly contracts with each (homogeneous) retailer. In a classic framework without asymmetric information, the manufacturer sells through a single exclusive retailer in order to eliminate the opportunism problem. When retailers are privately informed about their (common) marginal cost, however, the number of competing retailers also affects their information rents and the manufacturer may prefer an oligopolistic market structure. We characterize how the manufacturer's production technology, the elasticity of final demand, and the size of the market affect the optimal number of retailers. Our results arise both with price and quantity competition, and also when retailers' costs are imperfectly correlated.
Keywords: D43; L11; L42; L81; 330; asymmetric information; distribution network; opportunism; retail market structure; vertical contracting